VD_FINDINFO Jug / 2013 / 172 vom 2. April 2012 - VD Tribunal cantonal (2012)
ENQUÊTE PÉNALE, SAUVEGARDE DU SECRET, LIBERTÉ DE LA PRESSE | 10 CEDH, 293 CP, 184 CPP, 448 al. 2 CPP (CH), 73 al. 2 CPP (CH)